TRATEGI PASIF PENGURANGAN KETIDAKPASTIAN DAN SELF- DISCLOSURE DALAM PENJAJAKAN AWAL HUBUNGAN DI INSTAGRAM - Hanafi, Shelia Nur; Astinana Yuliarti (Journal of Media and Communication Studies, 2024)
Communication can essentially reduce uncertainty between two individuals who are first involved in a conversation, this is a concept coined by Richard Calabrese and Charles Berger in the theory of Uncertainty Reduction. This research will focus on passive uncertainty reduction strategy, which are strategy where when someone observes without that person knowing via online as well as the use of Instagram media which is used as a medium for someone to observe other people without that person's knowledge. If it is associated with a passive strategy on Instagram which will affect self-disclosure, it can make a relationship move closer than before so that this research can find out how far self-disclosure can develop if you have previously searched for information. Selection of passive strategy to reduce uncertainty is based on friendship, romantic, and professional relationships. Based on the results of the analysis carried out using qualitative research methods and descriptive type,, communicator will be motivated to seek information using passive strategy on Instagram due to considerations between uncertainty and hope. Then also found that the passive strategy on Instagram fulfill six of the eight axioms in the uncertainty reduction theory including axiom 1 (verbal communication), axiom 3 (information seeking), axiom 4 (familiarity), axiom 6 (similarity), axiom 7 (taste). ), and axiom 8 (social network interaction), as well as initiating self-disclosure in face-to-face meetings so that relationships can develop more quickly.